Reversible Switching between Nonporous and Porous Phases of a New SIFSIX Coordination Network Induced by a Flexible Linker Ligand - Song, Bai-Qiao; Yang, Qing-Yuan; Wang, Shi-Qiang; Vandichel, Matthias; Kumar, Amrit; Crowley, Clare; Kumar, Naveen; Deng, Cheng-Hua; GasconPerez, Victoria; Lusi, Matteo; Wu, Hui; Zhou, Wei; et al. (Journal of the American Chemical Society, 2020)
Closed-to-open structural transformations in flexible coordination networks are of potential utility in gas storage and separation. Herein, we report the first example of a flexible SiF -pillared square grid material, [Cu(SiF )(L) ] (L = 1,4-bis(1-imidazolyl)benzene), . exhibits reversible switching between nonporous ( ) and several porous ( , , , and ) phases triggered by exposure to N , CO , or H O. In addition, heating to 433 K resulted in irreversible transformation to a closed polymorph, . Single-crystal X-ray diffraction studies revealed that the phase transformations are enabled by rotation and geometrical contortion of L. Density functional theory calculations indicated that L exhibits a low barrier to rotation (as low as 8 kJmol ) and a rather flat energy surface. In situ neutron powder diffraction studies provided further insight into these sorbate-induced phase changes. combines stability in water for over a year, high CO uptake (ca. 216 cm /g at 195 K), and good thermal stability.